The Social and Mystic Brain in the Substance Dependent Patient - Franco, Gabriela (Consorcio de Universidades Mexicanas A.C., 2021)
Human beings activate a neural system when involved in social interaction known as the social brain, and similarly, mystic experiences stimulate the mystic brain. We postulate that both systems help humans to integrate into their support group, that integration allows them to avoid or control psychiatric disorders, and to reduce the risk of developing a substance use disorder (SUD). When this integration fails, as consequence of child abuse, negligence, and/or a poor social support network, subjects are more vulnerable to suffer a SUD. On the other hand, the belongingness to religious groups helps to maintain physical and mental well-being of believers, hence, preventing the development of SUD or rehabilitating the subject after suffering from it. Therefore, the aim of this review is to discuss the role of the social and mystic brain in individual integration to a social support group and how the failure of these systems represents a risk factor for developing or maintaining psychiatric disorders and SUD.